2003
DOI: 10.1292/jvms.65.83
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DDAVP Administrated Subcutaneously in Dogs with Aspirin-induced Platelet Dysfunction and Hemostatic Impairment due to Chronic Liver Diseases.

Abstract: ABSTRACT. To evaluate the hemostatic effects of desmopressin (DDAVP) in dogs with aspirin-induced platelet dysfunction and hemostatic impairment in chronic liver diseases, 3 µg/kg DDAVP was administrated subcutaneously. In aspirin-induced platelet dysfunction dogs (n=5), prolonged BMBT (buccal mucosal bleeding time) was shortened significantly after DDAVP injection (2.2 ± 1.2 min, P<0.05). In dogs with chronic liver diseases (n=4), activated partial thromboplastin time (APTT) tended to shorten by 0.9 to 3.0 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…However, correction of this deficit with platelet transfusion in people is not always associated with a decreased risk of bleeding . A case series evaluating 2 dogs (one with cirrhosis and one with CH) that had prolonged BMBT documented that coagulation times improved but did not normalize when these dogs were treated with desmopressin . Neither of the dogs in this study developed complications after liver biopsy …”
Section: Coagulation Abnormalities In Hepatobiliary Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…However, correction of this deficit with platelet transfusion in people is not always associated with a decreased risk of bleeding . A case series evaluating 2 dogs (one with cirrhosis and one with CH) that had prolonged BMBT documented that coagulation times improved but did not normalize when these dogs were treated with desmopressin . Neither of the dogs in this study developed complications after liver biopsy …”
Section: Coagulation Abnormalities In Hepatobiliary Diseasementioning
confidence: 99%
“…Platelet transfusions in thrombocytopenic patients are not typically used due to the expense and very short duration of effect, but may be considered in life‐threatening situations with platelet counts < 10.0 × 10 9 /L . If a thrombocytopathia is suspected, the use of desmopressin may be beneficial …”
Section: Coagulation Abnormalities In Hepatobiliary Diseasementioning
confidence: 99%
“…It has been reported that DDAVP shortened prolonged bleeding time in human patients with aspirin-induced PLT dysfunction and prolonged bleeding, and activated a PTT in cases of chronic liver diseases (Cattaneo et al 1990, Kam 1994, Manucci 1997. In dogs, the infusion of DDAVP at a dose of 0.6 μg/kg had no significant effect on PLT count and PCV, and a subcutaneous injection of DDAVP at a dose of 3 μg/kg in healthy dogs did not induce significant changes in PLT count (Sakai et al 2003).…”
Section: Discussionmentioning
confidence: 87%
“…In the dog, increases in the plasma content of FVIII and vWf seem to be dose-dependent (Johnson et al 1986), and because of this characteristic, DDAVP is widely used for the treatment of patients with von Willebrand diseases, haemophilia A. It has also been used with good haemostatic effect in a variety of different disorders characterized by impaired platelet function and prolonged bleeding time, including congenital platelet dysfunctions, uraemia, liver cirrhosis and platelet dysfunction caused by drugs such as aspirin, both in human (Sutor 2000) and dog (Johnstone 1999, Sakai et al 2003. The haemostatic effect of DDAVP probably involves additional cellular effects that remain to be discovered (Kaufmann and Vischer 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The use of desmopressin promptly reduced BMBT to times ranging from 3 to 4 minutes and allowed surgery to be carried out without abnormal bleeding in all animals . Although BMBT may be considered as a useful test for detecting primary hemostatic disorders resulting from aspirin‐induced platelet dysfunction, it appears that therapeutic doses of nonselective COX inhibitors such as ketoprofen do not consistently prolong BMBT. Preoperative ketoprofen administration to dogs undergoing ovariohysterectomy, despite causing inhibition of platelet function, neither increased BMBT nor caused abnormal intraoperative bleeding in comparison to placebo‐treated animals .…”
Section: Discussionmentioning
confidence: 99%